2014
DOI: 10.1161/jaha.114.001263
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 Induces Myofibrillar Disarray and Contractile Vector Variability in Hypertrophic Cardiomyopathy–Induced Pluripotent Stem Cell–Derived Cardiomyocytes

Abstract: BackgroundDespite the accumulating genetic and molecular investigations into hypertrophic cardiomyopathy (HCM), it remains unclear how this condition develops and worsens pathologically and clinically in terms of the genetic–environmental interactions. Establishing a human disease model for HCM would help to elucidate these disease mechanisms; however, cardiomyocytes from patients are not easily obtained for basic research. Patient‐specific induced pluripotent stem cells (iPSCs) potentially hold much promise f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
111
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 54 publications
11
111
0
4
Order By: Relevance
“…It should be noted that the R173W mutation identified in these DCM patients had not been previously reported, and was discovered in this family cohort following exome sequencing of the skin fibroblasts used to generate hiPSCs. In separate studies, hiPSC-CMs carrying DCM-associated mutations in the spliceosome RNA-binding motif protein 20 (RBM20), lamin A/C (LMNA/C), or desmin (DES) genes (243,275,304) also demonstrated abnormalities that closely recapitulate the morphological and functional phenotypes of the affected human heart, as outlined in hiPSC models of HCM associated with thick myofilament myosin heavy chain 7 (MYH7) (89,148) or myosin binding protein C3 (MYBPC3) (262) mutations showed that in vitroderived hiPSC-CMs are significantly enlarged, as seen in the diseased human myocardium. hiPSC-CMs also demonstrated increased myofibril content, contractile arrhythmias (DADs), Ca 2ϩ cycling perturbations, and intracellular Ca 2ϩ elevation, which were worsened by adrenergic stimulation (e.g., with isoproterenol) or environmental exposure to the potent vasoconstrictor endothelin-1 (ET-1) (310).…”
Section: B Cardiomyopathiesmentioning
confidence: 96%
“…It should be noted that the R173W mutation identified in these DCM patients had not been previously reported, and was discovered in this family cohort following exome sequencing of the skin fibroblasts used to generate hiPSCs. In separate studies, hiPSC-CMs carrying DCM-associated mutations in the spliceosome RNA-binding motif protein 20 (RBM20), lamin A/C (LMNA/C), or desmin (DES) genes (243,275,304) also demonstrated abnormalities that closely recapitulate the morphological and functional phenotypes of the affected human heart, as outlined in hiPSC models of HCM associated with thick myofilament myosin heavy chain 7 (MYH7) (89,148) or myosin binding protein C3 (MYBPC3) (262) mutations showed that in vitroderived hiPSC-CMs are significantly enlarged, as seen in the diseased human myocardium. hiPSC-CMs also demonstrated increased myofibril content, contractile arrhythmias (DADs), Ca 2ϩ cycling perturbations, and intracellular Ca 2ϩ elevation, which were worsened by adrenergic stimulation (e.g., with isoproterenol) or environmental exposure to the potent vasoconstrictor endothelin-1 (ET-1) (310).…”
Section: B Cardiomyopathiesmentioning
confidence: 96%
“…Additional cardiomyopathy models have been generated from patient-specific iPS cells with hypertrophic cardiomyopathy (HCM) [22, 39, 40]. Compared to healthy controls, iPS cell-derived cardiomyocytes from HCM patients showed increased cellular size, sarcomeric disorganization and greater nuclear localization of NFATC4, all signatures of a hypertrophic state.…”
Section: Ips Cell Models Of Cardiomyopathiesmentioning
confidence: 99%
“…64 (3), [207][208][209][210][211][212][213][214][215] model is required to fully understand the pathophysiology. The generation of human induced pluripotent stem cells (iPSCs) from patients with hereditary diseases, and the differentiation of these diseasespecific iPSCs into various types of cells holds the potential for elucidating the pathogenesis of complex human diseases 15) -20) . These iPSC-derived differentiated cells have enabled the supply of a sufficient number of human cells with genetic mutations for basic research and drug screening 21)- 24) .…”
Section: Introductionmentioning
confidence: 99%